Developmental Local Governance - Schoburgh, Eris D. author. aut Link
XI, 260 p.
Keywords: The primary purpose of this edited collection is to evaluate critically the relationship between local government and national economic development. It focuses on how the relationship between local government and development is structured, and the specific institutional arrangements at national and subnational levels that might facilitate local government's assumption of the role of development agent. In light of the contradictory outcomes of development and implied experimentation with new modalities, post-development discourse provides a useful explanatory framework for the book. Schoburgh, Martin and Gatchair's central argument is that the pursuit of national developmental goals is given a sustainable foundation when development planning and strategies take into account elements that have the potential to determine the rate of social transformation. Their emphasis on localism establishes a clear link between local government and local economic development in the context of developing countries.